An Operational System For Mapping Global Solar Radiation From GMS Satellite Data - Chumnong Sorapipatana; R.H.B Exell (ASEAN Journal on Science and Technology for Development, 1988)
An Operational System For Mapping Global Solar Radiation From GMS Satellite Data